Profiling of α-glucosidase inhibitors from ethyl acetate fraction of Buas-buas (Premna serratifolia) leaves using UHPLC-Q-Orbitrap HRMS and protein-ligand interaction with molecular docking - Dini Hadiarti,, Winarto Haryadi, Sabirin Matsjeh, Respati Tri Swasono, Nurdianti Awaliyah (Journal of Applied Pharmaceutical Science, 2023)
The Buas-buas (Premna serratifolia) leaves’ extract from maceration, percolation, and decontamination have proven to be α-glucosidase inhibitors. Since the efforts to isolate phytochemical constituents from P. serratifolia leaves as α-glucosidase inhibitors have not been carried out, a study is needed to determine the responsible compound for this activity which has been proven in vitro and in silico. Isolation of active compounds from ethyl acetate fraction has the best inhibition utilizing column chromatography and semipreparative high-performance liquid chromatography (HPLC). Identifying compounds from the isolate was investigated by ultra-high-performance liquid chromatography-Q exactive hybrid quadrupole-orbitrap high-resolution mass spectrometry (UHPLC-Q-Orbitrap HRMS). Interaction of α-glucosidase and active compounds was studied by molecular docking utilizing N-terminal maltase-glucoamylase [protein data bank (PDB) code: 2QMJ], C-terminal maltase-glucoamylase (PDB code: 3TOP), and isomaltase (PDB code: 3A4A). Analyzed by UHPLC-Q-Orbitrap HRMS, nine flavonoids were detected, which are centaureidin, chrysin, pectolinaringenin, glycitein, kaempferide, syringetin, tricin, casticin, and 3,5,4?-trimethoxy- 6,7-methylenedioxyflavone (estimated to be a new compound). Casticin–2QMJ, tricin–3TOP, and centaureidin–3A4A complexes have the lower binding energies of −5.29, −6.77, and −8.02 kcal/mol and inhibitory constant (Ki) of 131.54, 10.89, and 0.34 μM, sequentially.